A functional polymorphism in the promoter of RhoB is associated with susceptibility to Vibrio anguillarum in turbot (Scophthalmus maximus). Issue 93 (October 2019) - Zhang, Kai; Liu, Yuxiang; Liu, Xiumei; Peng, Meiting; Liu, Jinxiang; Zhang, Quanqi
Abstract: As an isoform of Rho family GTPases, RhoB plays a pivotal role in cytoskeletal organization, cell proliferation, apoptosis and immune response. However, the regulatory mechanisms of RhoB expression in aquatic animals are still unknown. In the present study, we first construct Vibrio anguillarum infection model in S. maximus, including susceptible and resistant individuals. Then the temporal expression of RhoB was detected after V. anguillarum challenge using qRT-PCR and found that RhoB transcripts were significantly induced in the liver, gill and blood despite of differential expression levels and responsive time points. In addition, the mRNA levels of RhoB in resistant individuals were significantly higher than in susceptible ones. The length of 2083 bp sequences of RhoB promoter was cloned and characterized. Moreover, DNA methylation of the RhoB promoter was measured by bisulfite sequencing (BSP) and hypo-methylated was detected in the CpG islands. Three SNPs (−1590, −1575 and −1449) and two haplotypes in the promoter region of RhoB were identified to be associated with V. anguillarum resistance in turbot by association analysis in group 17-R and 17-S. Deletion analysis indicated that these SNPs could negatively mediate the activity of RhoB promoter. Site-directed mutagenesis and qRT-PCR of individuals with different genotypes demonstrated that −1575 T/A polymorphism affected promoter activity. Further study showed that this mutation altered the binding site of the transcription factor CREB. Co-transfection of Sm CREB and RhoB promoter was performed in HEK293T cells which confirmed the −1575 allelic differences on transcriptional activity, with the susceptibility allele showing reduced activity. Taken together, our findings implicate that losing of binding of CREB to Sm RhoB promoter due to −1575T/A polymorphisms enhances Sm RhoB expression in resistant turbot, which provide insights into the effect of Sm RhoB expression in response to V. anguillarum infection. Highlights: Sm RhoB responded quickly and substantially after V. anguillarum challenge in turbot. Three SNPs and two haplotypes in Sm RhoB promoter were identified to be associated with V. anguillarum resistance. An allelic polymorphism account for the transcriptional activity of Sm RhoB in resistant and susceptible individuals.